RACISM IN EUGENE O’NEILL’S ALL GOD’S CHILLUN GOT WINGS - Eka Yuliana (Humaniora Scientia, 2020)
This research was aimed to find out experience of racism toward Jim Harris in All GodsChillun Got Wings, and to find out effects of racism toward Ella Downey. This research wasdescriptive. The data of this research were words, phrases, clauses, or discourse containingracism in the drama All Gods Chillun Got Wings. The source of the data was document, namelya drama entitled All Gods Chillun Got Wings written by Eugene O’neill’s. The technique ofcollecting the data was document analysis. Moreover, psychological approach and sociologicalapproach were applied to decide the strategy in analyzing the experience of racism and effects ofracism found in this drama. The analysis shows that (1) experience of racism toward Jim Harris.Furthermore, (2) the effects of racism toward major character Ella Downey. The conclusion isBlack people and white people cannot live together. White people always think black peoplecannot be a lawyer. If black people and white people marry they will get bad treatment and theywill be isolated by the society.